The effect of website quality, social media marketing, and personal selling on brand equity through brand loyalty: A study of B2B customers of PT gaya makmur tractors - Jimmy Fernando Pangaribuan; Dita Maharani; Amia Luthfia (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: The rapid expansion of digital communication technologies has fundamentally transformed marketing practices in business-to-business (B2B) industries. Despite this shift, the effectiveness of integrating digital channels with interpersonal communication in shaping long-term brand value remains insufficiently explained, particularly within complex industrial markets such as heavy equipment distribution. Existing studies tend to examine website quality, social media marketing, and personal selling in isolation, leaving a critical gap in understanding their combined influence and underlying relational mechanisms. Aims: This study aims to analyze the integrated effects of website quality, social media marketing, and personal selling on brand equity through brand loyalty, while clarifying the mediating role of relational commitment in a B2B context. Method: A quantitative explanatory approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 302 B2B customers of PT Gaya Makmur Tractors through a structured questionnaire, and analyzed to evaluate both direct and indirect relationships among constructs. Results: The findings demonstrate that all three communication channels significantly influence brand loyalty and brand equity. Social media marketing exhibits the strongest direct effect on brand equity, followed by personal selling and website quality. Furthermore, brand loyalty acts as a partial mediator, indicating that communication effectiveness operates through both immediate perception and sustained relational engagement. Conclusion: This study advances the understanding of B2B marketing by positioning brand loyalty as a central relational mechanism within an integrated communication system. The results suggest that brand value in industrial markets is not solely driven by information quality or promotional intensity, but by the ability to align digital credibility with personalized interaction to foster long-term commitment. From a practical standpoint, firms are encouraged to develop coordinated communication strategies that balance digital presence and interpersonal engagement as part of a unified decision-support system. This approach not only strengthens competitive positioning but also enhances the sustainability of customer relationships, offering a more holistic pathway for optimizing brand equity in complex B2B environments.